Optimization Model Based Techno-Economic Assessment for Optimal Siting, Sizing and Energy Market Participation of Battery Energy Storage System to Enhance Grid Flexibility - Alam, Md Ashfaqul (My University, 2025)
This thesis investigates a 20 kV Medium Voltage (MV) radial distribution network located in Porkholm, Finland, as part of the PEAK project in collaboration with the Distribution System Operator, Esse Elektro-Kraft Ab. The Porkholm 20 kV distribution network, which serves a combination of dispersed urban and scattered rural consumers, often faces significant operational challenges, including irregular load profiles and voltage instability. These issues compromise system reliability and efficiency, highlighting the growing need for enhanced network flexibility to accommodate fluctuating demand. To address these challenges, this study explores the integration of a Battery Energy Storage System (BESS) as a flexible solution that enhances grid stability while maximizing revenue through strategic participation in energy markets. A two-stage optimization framework is developed, incorporating piecewise linearized power flow modelling and Mixed-Integer Linear Programming (MILP), to determine the optimal siting, sizing and energy market participation of BESS. This technical approach is complemented by a comprehensive techno-economic analysis, aiming to balance operational constraints with market based economic performance. In the first stage, the optimal BESS location is identified by targeting nodes with the highest voltage deviation and minimum BESS size, thereby improving voltage stability and overall network flexibility. Simulation results confirm that strategic placement of BESS significantly enhances voltage profiles and system reliability. The second stage involves determining the optimal BESS size by simulating its participation in both the Day-Ahead Spot Market and the Frequency Containment Reserve for Normal operation (FCR-N) market. In this stage, a strategic market participation approach is developed to allocate BESS capacity effectively between the two markets, aiming to maximize revenue while maintaining grid support functions. Finally, the economic feasibility of BESS deployment is evaluated using key financial metrics. The Net Present Value (NPV) analysis confirms positive long-term returns, with a payback period of approximately 6 years under a 5% discount rate. The Levelized Cost of Electricity (LCOE) is calculated at 0.2788 euro per kWh over the project’s lifetime. These findings demonstrate that when BESS is optimally sited, correctly sized, and strategically integrated into energy markets, it can deliver both technical benefits and cost-effective energy services to the MV distribution network.
Keywords: storage; electricity market; distribution of electricity; electrical power networks; optimisation; flexibility; smart grids; voltage; fi=Sähkö- ja energiatekniikka|en=Electrical Engineering and Energy Technology|; Master´s Programme in Smart Energy